Citizenship in transformation in Canada - Hébert, Yvonne M., 1942- (University of Toronto Press, 2002)
Recent changes in concepts of citizenship have forced a reconsideration of Canadian political and educational policy. Weaving together the current debates on citizenship with contributions by leading independent thinkers in the field, Citizenship in Transformation argues persuasively that since conceptions of democratic citizenship are changing, so too should operational definitions of citizenship education. Focussing on four dynamic themes - conceptual foundations, institutional policies, social and cultural realities, and education - the contributors address two critical questions: What constitutes a 'good' citizen in today's liberal democracy? And, what social and educational policies are needed to sustain the lives of these citizens, while not impinging on liberal democratic principles? Bringing together a variety of perspectives from theoretical and conceptual foundations, this book will have broad implications for social and educational policies and institutions in Canada.